2020
DOI: 10.1021/acs.jpcb.0c04320
|View full text |Cite
|
Sign up to set email alerts
|

Water Dynamics Around Proteins: T- and R-States of Hemoglobin and Melittin

Abstract: The water dynamics, as characterized by the local hydrophobicity (LH), is investigated for tetrameric hemoglobin (Hb) and dimeric melittin. For the T 0 to R 0 transition in Hb, it is found that LH provides additional molecular-level insight into the Perutz mechanism, i.e., the breaking and formation of salt bridges at the α 1 /β 2 and α 2 /β 1 interface is accompanied by changes in LH. For Hb in cubic water boxes with 90 and 120 Å edge length it is observed that following a decrease in LH as a consequence of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…7). It is our hope that this work will provide a reference for the scientific community to identify cases that do not meet scientific standards (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). It is our hope that this work will provide a reference for the scientific community to identify cases that do not meet scientific standards (33).…”
Section: Discussionmentioning
confidence: 99%
“…Upon generation of a larger data sample, the previous conclusions of El Hage et al are shown not to hold ( Figure 7 ). It is our hope that this work will provide a reference for the scientific community to identify cases that do not meet scientific standards ( Pezzella et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the ensuing debate [51][52][53][54] highlights the importance of setting up systems correctly for simulation and, more importantly, applying ensemble approaches to get statistically significant results. The issue at stake is also important for the evaluation of the reliability of scientific research, as is clear from the follow up studies by the debaters [45,55]. As we noted above, without first handling the stochastic errors, it is not possible to assess correctly the nature and magnitude of the systematic errors, and to interpret findings convincingly.…”
Section: (B) Random Errorsmentioning
confidence: 99%
“…The transient dynamics of salt bridge formation and deformation are thus relayed to the surrounding liquid via changes in water's interfacial polarization response. These changes may play a role in modulating the water-mediated effects that drive conformational changes (38)(39)(40) or the nascent stages of protein-protein (41) or protein-ligand binding (2).…”
Section: Role Of Water-water Interactions In the Nonlinear Response Of Interfacial Water When Strong Surface-water In-mentioning
confidence: 99%